Liderazgo para la gobernanza colaborativa por la transparencia a nivel local: los retos del caso de Bogotá (2021)
This case study narrates and analyzes the public management challenge faced by the Veeduría Distrital de Bogotá and the Veedor Distrital, Jaime Torres-Melo, to implement the Bogotá Transparency Index -ITB- during the period between 2016 and 2019. The project was structured as part of an action plan designed by the Veeduría Distrital to promote the issues of transparency, access to public information, mitigation of corruption risks and promote the exercise of social control from its mission as a control body preventive (Torres Melo, 2020). The implementation of the ITB materialized as a result of a collaborative governance exercise, in which Transparencia por Colombia -a civil society organization-, the Bogotá Chamber of Commerce and ProBogotá - private sector- and, the Veeduría Distrital -organization of control of the public sector-, around the fight against corruption as a public policy problem.